BS EN IEC 55016-1-4. Specification for radio disturbance and immunity measuring apparatus and methods. Part 1-4. Radio disturbance and immunity measuring apparatus. Antennas and test sites for radiated disturbance measurements (25th December 2020) - British Standards Institution,
No abstract available